Budget for children in Assam :Children's Security Neglected In Assam Budget:An Analysis from A Child Rights Perspective 2004-05 to2008-09 - Batra, Tripta; HAQ: Centre for Child Rights; Ford Foundation (New Delhi : Haq: Centre for Child Rights, 2007)
Covers the period, 2000-2007.
[1] India -- [2] Andhra Pradesh -- [3] Himachal Pradesh -- [4] Orissa
Cover title.
Includes statistics.
Keywords: Child welfare -- India -- Finance; Federal aid to child welfare -- India; Poor children -- Services for -- India; Budget -- India